Largely enhanced dielectric properties of polymer composites with HfO2 nanoparticles for high-temperature film capacitors - Ren, Lulu; Yang, Lijun; Zhang, Siyu; Li, He; Zhou, Yao; Ai, Ding; Xie, Zongliang; Zhao, Xuetong; Peng, Zongren; Liao, Ruijin; Wang, Qing (Composites science and technology, 2021)
Polymer dielectrics are preferred materials for high-energy-density capacitive energy storage. In particular, high-temperature dielectrics that can withstand harsh conditions, e.g., ≥150 °C, is of crucial importance for advanced electronics and electrical power systems. Herein, high-temperature dielectric polymer composites composed of polyetherimide (PEI) matrix and hafnium oxide (HfO2) nanoparticles are presented. It is found that the incorporation of HfO2 with a moderate dielectric constant and a wide bandgap improves the dielectric constant and simultaneously reduces the high-field leakage current density of the PEI nanocomposites. As a result, the PEI/HfO2 composites exhibit superior energy storage performance to the current high-temperature engineering polymers at elevated temperatures. Specifically, the nanocomposite with 3 vol% HfO2 displays a discharged energy density of 2.82 J/cm3 at 150 °C, which is 77% higher than neat PEI. This work demonstrates the effectiveness of incorporation of the nanofiller with a medium dielectric constant into the polymer on the improvement of high-temperature capacitive properties of the polymer composites. [Display omitted]